Clinical impact of studying epithelial–mesenchymal plasticity in pluripotent stem cells. (28th March 2015) - Kovacic, Boris; Rosner, Margit; Schipany, Katharina; Ionce, Loredana; Hengstschläger, Markus
Abstract: Background: The ability of cells to travel long distances in order to form tissues and organs is inherently connected to embryogenesis. The process in which epithelial‐like embryonic cells become motile and invasive is termed 'epithelial‐to‐mesenchymal transition' (EMT), while the reversion of this programme – yielding differentiated cells and organs – is called 'mesenchymal‐to‐epithelial transition' (MET). Design: Here, we review the processes of EMT and MET in development and cancer and combine them with knowledge from pluripotent stem cell research. Results: Research has shown that these processes are activated in many cancers leading to dissemination of cancer cells throughout the body and formation of metastasis. While the regulation of EMT during cancer progression has been extensively studied for decades, many fundamental processes that govern normal development are only poorly understood. Recent discoveries, such as reprogramming to pluripotent stem cells and identification of ground and primed states of pluripotent stem cells, have redirected much attention to EMT and MET. Conclusion: Findings from pluripotent stem cell research and EMT/MET should be combined in order to design future strategies aimed to improve our understanding of cancer progression and to help develop novel anticancer strategies.